2013
DOI: 10.1089/dia.2012.0331
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Metabolic Effects of Continuous Subcutaneous Insulin Infusion Therapy in Type 1 Diabetes

Abstract: CSII in type 1 diabetes is associated with improved glycemic control with no increase in hypoglycemia. HbA1c improvement declined over time, suggesting a need for re-education after CSII commencement. The iMDI program did not have significant glycemic benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
0
15
3
3
Order By: Relevance
“…In some published studies, the benefits of CSII either were lost or were minimal at 3-5 years of follow-up [18][19][20]. By contrast, we observed benefits of CSII on HbA 1c for up to 10 years of follow-up.…”
Section: Previous Studies Relating Hba 1c Change To Duration Of Csii contrasting
confidence: 65%
“…In some published studies, the benefits of CSII either were lost or were minimal at 3-5 years of follow-up [18][19][20]. By contrast, we observed benefits of CSII on HbA 1c for up to 10 years of follow-up.…”
Section: Previous Studies Relating Hba 1c Change To Duration Of Csii contrasting
confidence: 65%
“…Other European centres have shown variable results with reductions in HbA 1c of –0.6% to –0.9%, including a reduction in HbA 1c that was not sustained beyond 3 years in Spain , a sustained reduction in HbA 1c of –0.6% in Slovenia and a 5‐year reduction of –0.5% in two large studies in France . Meanwhile, a Swedish study showed a modest –0.2% change in in HbA 1c in 331 patients after 5 years , and a smaller Australian study of 126 CSII users had a significant improvement in HbA 1c of –0.64% at 6 months that was sustained to 3 years . These variable findings are likely attributed to differences in demographics, clinical practice and guidelines, follow‐up frequency, and access to structured education.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Recent retrospective studies have reported the long-term efficacy and safety of CSII in adult and younger patients, but quality of life and satisfaction were not questioned in these studies. [11][12][13] The design of our study included data collection on CSII utilization and satisfaction. We observed that patients with CSII had a high level of satisfaction several years after CSII initiation and were prone to encourage their peers to move to pump therapy.…”
Section: Discussionmentioning
confidence: 99%